Electrochemical detection of nitrate and nitrite at a copper modified electrode - Davis, J; Moorcroft, M; Wilkins, S; Compton, R; Cardosi, M (2000)
The development of a reagentless electrode system for the determination of nitrate is presented. The approach is based upon the deposition of a macroporous copper deposit which shows marked selectivity for nitrate ion under mildly acidic conditions (pH 3) with a linear range extending from 10 to 200 μM nitrate. Fabrication of the layer is both inexpensive and simple and is relatively substrate independent (Cu, Au, glassy carbon) as the response is attributed to the electrodeposited support. The influence of potential interferents such as chloride, nitrite and complexing agents such as citric acid were examined. In particular, the reduction of nitrite was found to occur at potentials significantly less negative than those required for nitrate reduction and as a result clear resolution of both voltammetric peaks is obtainable. The lack of direct interference between the two ions combined with wide peak separation (200 mV) provides a system that may offer some potential in speciation studies. The analytical applicability of the proposed system was demonstrated through the standard addition determination of nitrate in a number of authentic samples with the nitrate concentrations independently corroborated using established Griess assay spectroscopic protocols.